Standardization of Mesh Size of Gill Nets for the Commercial Exploitation of Kawakawa, Euthynnus affinis (Cantor) in Thoothukkudi Coastal Waters, Southeast coast of India - N., Neethiselvan; D., Jude; P., Gopalakrishnan; G., Sugumar (Fishery Technology, 2025)
Euthynnus affinis forms notable fishery in Thoothukkudi coastal waters with peak season from June to September. Euthynnus affinis is captured in small meshed gillnets popularly called 'PODIVALAI' with mesh size ranging from 60 mm to 115 mm. The present study deals with the standardization of mesh size to capture the commercially significant length group (476-600 mm) of E. affinis and its enmeshing pattern in gillnets with three different mesh sizes. The optimum mesh size for the commercial exploitation of Â£. affinis in Thoothukkudy coastal waters is found to be 104.2 mm. Further, the study recommends to discourage the use of gill net with 50 mm mesh size for the capture of E. affinis as this net captures the juveniles of Â£. affinis.